Sex-specific differences in hyperoxic lung injury in mice: Role of cytochrome P450 (CYP)1A. (4th May 2015) - Lingappan, Krithika; Jiang, Weiwu; Wang, Lihua; Couroucli, Xanthi I.; Moorthy, Bhagavatula
Highlights: Cytochrome P450(CYP) 1A shows gender-specific changes in hyperoxic lung injury. WT female mice show higher CYP1A expression in hyperoxia compared to males. The female advantage is lost or reversed in Cyp1a1-/- and Cyp1a2-/- mice. Abstract: Sex-specific differences in pulmonary morbidity in adults and preterm infants are well documented. Hyperoxia contributes to lung injury in experimental animals and humans. Cytochrome P450 (CYP) 1A enzymes have been shown to play a mechanistic role in hyperoxic lung injury (HLI) in animal models. Whether CYP1A enzymes contribute to gender-specific differences in relation to HLI is unknown. In this investigation, we tested the hypothesis that mice will display gender-specific differences in HLI, and that this phenomenon will be altered in mice lacking the genes for Cyp1a1 or 1a2 . Eight week-old male and female wild type (WT) (C57BL/6J) mice, Cyp1a1 -/-, and Cyp1a2 -/- mice were exposed to 72 h of hyperoxia (FiO2  > 0.95). Lung injury and inflammation were assessed and pulmonary and hepatic CYP1A1 and CYP1A2 levels were quantified at the enzyme activity, protein and mRNA level. Upon exposure to hyperoxia, liver and lung microsomal proteins showed higher pulmonary CYP1A1 (apoprotein level and activity) in WT females compared to WT males and a greater induction in hepatic CYP1A2 mRNA levels and activity in WT females after hyperoxia exposure. The gender based female advantage was lost or reversed in Cyp1a1 -/- and Cyp1a2 -/- mice. These findings suggest an important role for CYP1A enzymes in the gender-specific modulation of hyperoxic lung injury.